Case Study Analysis of the Use of Cloud Computing for Assessing Big Data Risks - Fadi Fataftah; Bassey Isong (Journal of Information System and Informatics, 2023)
Risks associated with adopting big data and cloud computing and exposing sensitive information must be evaluated as usage of these technologies continues to rise rapidly within businesses. Also, the company needs to investigate the potential consequences of cyber security threats, considering the severity of those risks. There has been no comparative analysis of the risk assessment methods available to businesses in various nations. Thus, the researcher in this study asked forty people from four countries (Canada, Jordan, South Africa (SA), and the United Kingdom (UK)) questions on the risk assessment procedures at their respective organizations using semi-structured interviews. After compiling and analyzing the data, it became clear that Canada and the UK were the frontrunners in adopting big data and cloud computing. It also demonstrated that Jordan and SA are in the early phases of an evolving adoptive relationship. Recommendations are made to strengthen the organization's standing in light of the different risk assessment frameworks used in each country.